Sebuah Penantian RUU Penghapusan Kekerasan Terhadap Perempuan: Nalar Keadilan Hak-Hak Perempuan Korban Kekerasan Dalam Rumah Tangga - Serlika Aprita (UIN Syarif Hidayatullah Jakarta, 2022)
Domestic violence (KDRT) occurs in a gendered household and causes sorrow and suffering for its victims, who are mostly women, and perpetrators, who are mostly men. The Law on the Elimination of Domestic Abuse protects human dignity, husband and wife's rights in the home, and violence or discrimination against women (KDRT). In addition to raising community understanding and knowledge of gender equality and justice to promote women's welfare and protection from violence, women's participation in all disciplines, especially development, must be boosted. The government should protect women from assault and demeaning treatment. Domestic violence may happen anywhere. Domestic violence prevents victims and perpetrators from knowing one other's social, economic, or educational status. This endeavor educates the public about domestic abuse and its psychological repercussions on children.